2011
DOI: 10.1007/s10661-011-2266-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive endocrine disruption in smallmouth bass (Micropterus dolomieu) in the Potomac River basin: spatial and temporal comparisons of biological effects

Abstract: A high prevalence of intersex or testicular oocytes (TO) in male smallmouth bass within the Potomac River drainage has raised concerns as to the health of the river. Studies were conducted to document biomarker responses both temporally and spatially to better understand the influence of normal physiological cycles, as well as water quality and land-use influences. Smallmouth bass were collected over a 2-year period from three tributaries of the Potomac River: the Shenandoah River, the South Branch Potomac and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 86 publications
(109 reference statements)
8
105
0
Order By: Relevance
“…The most commonly reported effects are those resulting from exposure to estrogenic/antiandrogenic chemicals. Feminization of male fishes as evidenced by testicular oocytes or intersex (Jobling et al, 1998;Kavanagh et al, 2004;Dietrich and Krieger, 2009;Blazer et al, 2012) and production of Vtg (Denslow et al, 1999;Jones et al, 2000;Dang et al, 2011;Vajda et al, 2011) has been observed in numerous fish species. In a few cases, population effects are reported (Kidd et al, 2007;An et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported effects are those resulting from exposure to estrogenic/antiandrogenic chemicals. Feminization of male fishes as evidenced by testicular oocytes or intersex (Jobling et al, 1998;Kavanagh et al, 2004;Dietrich and Krieger, 2009;Blazer et al, 2012) and production of Vtg (Denslow et al, 1999;Jones et al, 2000;Dang et al, 2011;Vajda et al, 2011) has been observed in numerous fish species. In a few cases, population effects are reported (Kidd et al, 2007;An et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, endocrine disrupting compounds (EDCs) are an increasing concern for wildlife, since population-level impacts of these compounds have been documented (Kidd et al, 2007;Lange et al, 2011;Blazer et al, 2012). Endocrine disrupting compounds are most often associated with municipal and industrial wastewater effluent, can feminize male fish in receiving waters (Sumpter, 2005;Desbrow et al, 1998;Blazer et al, 2007), and lead to local extinction (Kidd et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Strong interest in particular circumstances surrounding exposures of aquatic animals to EDCs has been driven, in part, by news and media accounts of reproductive abnormalities in fishes (e.g., Blazer et al, 2012) and amphibians (e.g., Skelly et al, 2010), and the mysterious loss of amphibian populations around the globe.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%